2016
DOI: 10.1039/c6ra07907e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding interactions affect the hierarchical self-assembly and secondary structures of comb-like polypeptide supramolecular complexes displaying photoresponsive behavior

Abstract: Hierarchical lamellae-within-lamellae structure for the PTyr/AzoPy-C16 supramolecular complex, featuring long-range-ordered lamellae arising from the PTyr within lamellae arising from AzoPy-C16 units oriented in a perpendicular manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Because of their ability to undergo trans-to-cis photoisomerization, azobenzene chromophores have been used widely as building blocks in various stimuli (photo)-responsive supramolecular compounds. Hartley et al discovered the photoisomerization of the azo chromophore, which experiences photoinduced trans-to-cis isomerization under irradiation with a UV lamp and cis-to-trans isomerization upon being left in the dark or heating . The photoresponsive nature of azobenzene chromophores can result in remarkable changes in visual color, dipole moment, and molecular orientation .…”
Section: Introductionmentioning
confidence: 99%
“…Because of their ability to undergo trans-to-cis photoisomerization, azobenzene chromophores have been used widely as building blocks in various stimuli (photo)-responsive supramolecular compounds. Hartley et al discovered the photoisomerization of the azo chromophore, which experiences photoinduced trans-to-cis isomerization under irradiation with a UV lamp and cis-to-trans isomerization upon being left in the dark or heating . The photoresponsive nature of azobenzene chromophores can result in remarkable changes in visual color, dipole moment, and molecular orientation .…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of polypeptide secondary structures through hydrogen bonding with additives has been reported. [43][44][45] For example, a phenolic resin with hydrogen bonding sites was blended with poly(glutamate)s to control the secondary structure. 43 In this blend, the stabilization of a-helical conformations was dependent on the rigidity of the protecting or side chain groups and the content of phenolic resin, which impacted the hydrogen bonding interactions between the polypeptide and phenolic resin.…”
Section: Resultsmentioning
confidence: 99%
“…then there will be six equations and only six unknowns. Thus, equation (13) in this case can be solved as the number of unknowns matches that of the equations.…”
Section: Equilibrium Equationsmentioning
confidence: 99%
“…Through the development of science and technology, it has been gradually found that chiral morphologies are ubiquitous in nature, and they can span multiple orders of magnitude in scale. Furthermore, there exist not only macro chiral morphologies, such as plants, winding vines, and rotating snail shells [7][8][9], but also micro chiral morphologies, such as DNA, polypeptide, actin filaments, and bacterial flagella [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%